Integrated mentoring strategies for enhancing the digital competitiveness of MSMEs - Ismarina; Dini Rachmaniah; Dewi Anggraini (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2026)
Micro, Small, and Medium Enterprises (MSMEs) serve as the primary engine of Indonesia's economy, yet they remain hindered by low digital literacy and traditional management practices. This community service program aimed to accelerate the digital transformation of MSMEs through a structured, participatory mentoring framework. The intervention was executed in five strategic phases: socialization, intensive training, technology implementation, monitoring and evaluation, and sustainability planning. Through this approach, MSME partners successfully integrated digital ecosystems, including e-commerce platforms (Shopee and Tokopedia), social media marketing, and digital financial management applications. The results demonstrate a significant shift in business capacity, particularly in precise production cost calculation, professional branding, and digital content creation. Post-program evaluation revealed that over 70% of participants experienced expanded market reach and increased sales volume. Sustainability is secured through the formation of "Digital Champion" groups and the integration of program outcomes into university curricula. This initiative proves that systematic assistance is vital for transitioning traditional MSMEs into the digital landscape. To foster long-term economic resilience, this model recommends cross-institutional collaboration and collective branding strategies as a blueprint for MSME empowerment in other regions.